Safe Nursing Practices Applied for Patients Post Hip Joint Replacement - Weheida, Soheir Mohamed; Abou-Zeid, Nesreen Abdel-Monaem; El Abassy, Esam Mohamed Kamel; Ashour, Magda Fekery (International Journal For Research In Health Sciences And Nursing, 2018)
improving the safety of healthcare delivery saves lives. Nurses are in a key position to improve patient safety in hip replacement which considered one of the most successful orthopaedic procedures performed today. Aim: the current study was aimed to assess safe nursing practices applied for patients post hip joint replacement. Design: A descriptive research design was used. Study setting: This study was conducted at inpatient orthopaedic units of El-Hadara Orthopaedic and Traumatology University Hospital. Sample: all (52) available nurses who were involved in providing direct care for patients post hip joint replacement was included. They were classified according to level of education into 2 technical and 50 diploma nurses. One tool was used titled "Safe nursing practices applied for patients post hip joint replacement observational checklist" in addition to nurses' socio demographic data. Results: the study revealed that all the studied nurses had poor unsafe nursing practices in relation to postoperative care applied for patients post hip joint replacement. The mean and standard deviation of safe hospital environment maintained by nurses during day one postoperative were higher (42.84 ± 4.84) than the pre discharge day (40.49 ± 4.84). Conclusion: There was significant relation between the nurses' safety practices and their age, years of experience; as the practice level increased with increasing age and years of experience. Recommendations: Improving nurses' practices through encouraging them to participate in educational programs through workshops, lectures and recent researches related to safety postoperative hip replacement.